Study on the Creep Behavior of a Ni3Al-Based Single Crystal Alloy at 850°C/450 MPa - Liwu Jiang; Yu Yang; Meiling Wu; Min Cai (International Journal of Photoenergy)
The creep behaviors of Ni3Al-based single crystal alloy IC6SX with [001] and [111] orientations under the condition of 850°C/450 MPa were investigated. The effect of crystal orientation on the creep lives, fracture morphology, fracture mechanism, and dislocation evolution of the alloys with different orientations was analyzed systematically. The results showed that the creep lives of the alloy were closely related to the crystal orientation under the condition of 850°C/450 MPa. The creep lives of the single crystal alloys with [001] and [111] orientations were 56.3 h and 126.9 h, respectively. Moreover, the fracture morphologies of the two alloys with [001] and [111] orientations were different. The results showed that some holes formed at the fracture surface of the alloy with [111] rather than [001] orientation. Furthermore, the surface near the fracture of the two alloys with [001] and [111] orientations was serrated. Therefore, the fracture mechanism of the single crystal alloys with [001] and [111] orientations was ductile fracture. In addition, a large number of dislocations cut into the γ′ phase. Therefore, the cutting mechanism of dislocations in the alloys with [001] and [111] orientations was the creep deformation mechanism.